Pengaruh Teman Sebaya (peer Influence) Terhadap Ketidakhadiran Pesertadidik Sekolah Menengah Pertama (SMP) di Kec. Sangir Kab. Solok Selatan - Raudhatul Jannah, Hanifah; Dianto, Mori; Mulyani, Rila Rahma (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
Peer influence is often a factor that influences students' decisions, including in the issue of absenteeism, which is a major challenge in the Junior High School (SMP) environment. This study aims to examine how peer influence influences student absenteeism in Junior High Schools in Sangir District, South Solok Regency. In this study, a quantitative research design was used using a simple linear regression analysis to see the effect of variable X on variable Y. The subjects in this study were 41 students of grades VII and VIII of Junior High Schools (SMP) in Sangir District, South Solok Regency. The sampling technique was carried out using the Cluster Sampling Technique. The results of this study indicate that there is a significant influence (Ha) between peer influence on student absenteeism in Junior High Schools (SMP), with a significance value of 0.044 <0.05, indicating that (Ha) is accepted. It can be concluded that 1) Peer influence of students is in the high category with a percentage of 85.37%, 2) Student absence is in the low category with a percentage of 80.49%, 3) The results of the analysis show that there is a significant influence (Ha) between peer influence on student absence. By finding the results of the significant influence of the circle of friends on the level of absence, this study contributes by providing a strong data foundation for schools to design strategic guidance and counseling programs, utilizing peer influence as a force to encourage optimal attendance